Propriedades mecânicas e durabilidade do concreto branco com adições pozolânicas - FERREIRA, Taiza Naiana da Silva (Universidade Federal do Pará, 2015)
The present work aims at investigating the behavior of White Portland cement concrete with addition of metakaolin and silica fume, evaluating the mechanical behavior, the behavior regarding water absorption and porosity level and durability in concrete with this binder. For this purpose, assays were performed in plastic state (consistency and density) and hardened (compressive strength, diametral tensile strength by, modulus of elasticity, water absorption, carbonation and penetration of chloride). Reviews of its compressive strength and tensile strength at the ages of 7 and 28 days by IPT/EPUSP method that uses traces 1:5, 1:3.5 and 1:6,5 were performed. The modulus of elasticity at 28 days. Besides these permeability was evaluated by absorption test; through accelerated durability testing of chlorides and carbonation, porosity was verified by carrying out the scanning electron microscopy. In general, it was found that even the resistance of concrete with the lowest aggregate/binder (poor trait), the proportion is above the more usual resistance in the metropolitan region of Belém which is around 25-30 MPa, whereas white cement used is structural, so it is justified to reach these values even with poor trait. With regard to permeability, the results demonstrated that as resistance, this is dependent on the type of cement used and the additions used. The highest permeability values were obtained in specific reference (without addition). To study the porosity was seen that concrete reference presents more compact and less noticeable pores, especially those with higher aggregate/binder ratios. Already in the micrographs of CMT concrete and CSA, you can see a smaller amount of pores in the region occupied by folder Finally, a comparison was made of the mechanical properties, water absorption capacity and porosity of white Portland cement (CPB).